WATER QUALITY MODELING AT THE CILIWUNG RIVER ESTUARY DUE TO THE CONSTRUCTION OF THE JAKARTA SEA WALL - Prasetya Darman, Luky
The Government of the Republic of Indonesia through the National Capital Integrated Coastal Development (NCICD) Program began in January 2013. One of the water quality problems due to the construction of this sea wall is the high pollution of BOD (Biological Oxygen Demand) and COD (Chemical Oxygen Demand) which in turn can reduce DO (Dissolved Oxygen). When the waters are still open (without sea walls), pollutants from river water will be diluted by water from the sea. Conversely, when the waters become closed, the concentration of pollutants will accumulate. The existence of a gap/cavity for the entry and exit of water in the design is a solution that needs to be studied whether it is sufficient to degrade pollutants from the river. The purpose of this study is to identify the concentration of pollutants from the Ciliwung River due to construction of the Jakarta Sea wall. The concentration of pollution in the river was analyzed using QUAL2Kw software which then the results will be input for analysis at sea using MIKE 21 software. Ocean current simulation results show that there is a decrease of 0.00731 m/s in the sea wall. There was a significant increase in BOD and COD concentrations with the construction of the Jakarta Sea wall, namely 128%, 316%, and 666% for BOD concentrations with seawall scenario is 1.931 mg/L, 0.327 mg/L, and 0.073 mg/L to 4.415 mg/L, 1.363 mg/L and 0.561 mg/L also COD concentration increase 33%, 41% dan 48% with concentration value 21.253 mg/L, 18.181 mg/L and 17.203 mg/L to 28.334 mg/L, 25.731 mg/L and 25.565 mg/L.